MENELUSUR JEJAK MISTISISME MONISME DARI KACAMATA FILSAFAT KETUHANAN - U. P. Charles Silalahi (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
Understanding of mysticism take us cross borders and dogmatic barriers to see how the richness of qualities are displayed in silence and solitude. An attempt to connect God with a contemplating heart through austerities, meditation and self-torture is an attempt to mediate oneself with the Divine Thing. This divine treasure from the wealth of spirituality, open a discussion to heal the wounds of God's rationalization by dwarfing the Infinite into a finite mind. It is as if the rationalization of God is a form of perfect capture that is not challenged by the understanding itself. Now we are brought to look at eclecticism and the requestion of the diversity of divine perspectives to find common understanding in treating God, the universe and others. God in the capture of mysticism monism is implemented in various forms, and they are placing the catch with the deepest reverence and exaltion that is reflected in their understanding of karma. Karma is a dogmatic balancing equilibrium that is often interpreted gratuitously to destroy nature in the name of craving for money and eliminating others in the name of views. From them,we learn to manage nature and respect others because for mysticism true warfare is war against oneself, not others for any reason.